UPAYA BADAN KEPEGAWAIAN DAERAH UNTUK MEMAKSIMALKAN SISTEM INFORMASI MANAJEMEN KEPEGAWAIAN (SIMPEG) DALAM PENEMPATAN PNS DI LINGKUNGAN PEMERINTAH KABUPATEN SANGGAU PROVINSI KALIMANTAN BARAT - Utami, Aullia Reza; Nurhadianto, Nurhadianto (Fakultas Politik Pemerintahan, 2017)
ABSTRACT The information system of employee affair management is an aplication by using a web basic to manage all process to employee affair when consist of planning, development, management by using the technology information in process the employee data become an information. SIMPEG itself provides all information that related to the employee in PEMKAB Sanggau and gives information that related to the employee placement. The main problems in this research is what does the BKD of Sanggau region do related to the implementation of the information of system of employee affair management in employee placement and the inhibiting factor and efforts that is done to make the SIMPEG effectivelly in employee placement. Therefore, the purpose of this researchis to know, elaborate placement in BKD of Sanggau region. SIMPEG gets input such as employees data, which next will be process become on information that is done to the employee placemen.This research is done in BKD of Sanggau region especially in the scope of information and employee data. This researchis a descritive qualitative research by data taking through interview, documentation and observation. The technique of data taking is by using the purpose sampling technique. From this research, that effectiveness of SIMPEG in employee placement in BKD of Sanggau region is not effetive,is not optimal yet in the implementation which caused by inhibiting factor that is a lack of technology resources which is a main supporting to materialize SIMPEG and employee lack a close relation in coordination and communication in gining data and employee information. Keywords: information, system, SIMPEG.